Enzyme blood level disorder as a marker of metabolic processes severity in multiple sclerosis - Markovskaya, E.V (Международный медицинский журнал, 2014)
Dynamics of membrane−bound enzymes activity changes in the blood of 67 patients with multiple sclerosis was investigated depending on the variety and duration of the disease. It was noted that the most pronounced enzymatic dysbalance was observed in patients with cerebrospinal multiple sclerosis and in patients with the disease duration over 10 years, which is a marker of disease severity and degree of the pathological process generalization. Decreased CPK level in patients with all varieties of the disease, regardless of multiple sclerosis duration, reflects the degree of reduction of metabolic and energy processes rate in the cells of muscular and nervous tissues, possibly due to increased catabolism and, as a consequence, development of movement disorders.